The potentials of emulsified modified bitumen (EMB) for coating and insulation: An overview - Obi, Nasreldeen Ishag; Mohd Najib, Razali; Nour, Abdurahman Hamid (Elsevier Ltd, 2022)
Fungi mould and bacterial growth in the inner wall of buildings and operation theatres is a serious problem in the health sector. Too much moisture and dirt stimulate the growth of microorganisms. Therefore, the use of bitumen or emulsified modified bitumen product because of its adhesive properties and effective performance in coating and insulation is a promising technique to tackle this problem. However, the vast majority of bitumen and its modified products are mainly used in road paving, roofing application, and roads construction applications. Thus, the EMB product for the purpose of coating, soundproofing, and insulation needs to be properly addressed. Results obtained from this critical review have revealed the ability of EMB in insulation and coatings, as EMB paints showed a better performance than non-modified bitumen emulsion in terms of coating adhesion, aging, and heat insulation. Since the modified emulsions from waste substances is comparable to neat bitumen emulsions, the developed EMB from industrial waste will address natural resource dependency as well as the enormous environmental problem emerging from the overuse of natural resources. Further works nevertheless are needed to gain a better understanding of the mechanisms of EMB formulation in order to promote optimum industrial application.